Academic activism as a necessity in community health research - Fernández-Sánchez, Higinio (2022)
Academic activism in health research seeks to promote equity and social justice with participating communities. A bilateral relationship between academia and communities is reached when knowledge is developed from the participants and for the participants. The aim of this article is to discuss strategies to use academic activism in community health research. We propose several strategies: the researchers’ reflexivity and positionality; the engagement of stakeholders; the immersion of the researcher in the field; and the development and transfer of knowledge. We focus the discussion on the transformative power of academic activism and its key elements that community researchers can consider. Innovative and contemporary approaches in community health research highlight the need to develop knowledge from a critical and reflective perspective. Community health professionals can take up these strategies to pursue a positive social change in the health of individuals, families, and communities.